PERLINDUNGAN KONSUMEN TERHADAP KLAUSULA BAKU DALAM PERJANJIAN - Komang Pebri Gunawan; Si Ngurah Ardhya; I Gusti Ayu Apsari Hadi (Jurnal Pacta Sunt Servanda, 2024)
The development of modern trade practices has encouraged the widespread use of standard contracts as an efficient instrument in transactions between business actors and consumers. However, the unilateral drafting of standard clauses often results in an imbalance of bargaining power that may disadvantage consumers, particularly through the limitation or transfer of business actors’ liability. This condition raises legal issues concerning consumer protection and the limitation of the principle of freedom of contract. This study aims to analyze the regulation of standard clauses in contracts and the forms of consumer legal protection under Law Number 8 of 1999 on Consumer Protection. The research employs a normative juridical method using statutory and conceptual approaches, supported by a literature review of primary, secondary, and tertiary legal materials. The findings indicate that the Consumer Protection Law provides strict limitations on the inclusion of unfair standard clauses through prohibitions on their substance, requirements of clarity and transparency, and legal consequences in the form of nullity by law. In addition, both preventive and repressive legal protections are available, including dispute resolution through the Consumer Dispute Settlement Body. Therefore, consumer protection against standard clauses represents a state effort to achieve justice and balance in contractual relationships.